Matrix-free laser desorption/ionisation mass spectrometry on rough or porous semiconductor substrates: theory and applications - Law, Kai (2008)
This project aimed to develop a high throughput, laser based, matrix-free, mass spectrometric technique using nanoporous and nanostructured semiconductor substrates for rapid, sensitive, high resolution and accurate mass analytical approach for complex biological matrices.